The sign of four spirits - Delany, Vicki, 1951- (Delany, Vicki, 1951- Sherlock Holmes Bookshop mystery, 2024)
"When a psychic fair arrives in West London, Gemma Doyle, owner of the Sherlock Holmes Bookshop and Emporium, wants nothing to do with it. But somehow, at the urging of Donald Morris, an enthusiastic Sherlockian, she finds herself talked into attending a séance, along with baker and best friend Jayne Wilson, store assistant, Ashleigh, and former pop star Bunny Leigh. But to her surprise, Gemma finds herself banned from the séance and shown the door. Curious, she listens in from outside the room. The medium informs a disappointed Donald that Sir Arthur Conan Doyle will not be able to make it tonight. Then, Gemma hears a voice cut off, a cry for help, a scream. Gemma bursts into the library to see that someone has collapsed on the table--dead. The windows are all locked, and Gemma was guarding the only door. Someone in this room is a murderer. But who? The game is once again afoot for Gemma Doyle, as she hunts a killer. But, this time, is the killer of flesh and blood or had the medium summoned doom from beyond the veil?"--